Produktivitätseffekte betrieblicher Zusatzleistungen - Roman Lutz (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– This paper analyses the productivity effects of five different types of employee benefits. The IAB establishment panel for the year 2000 is used as the data set. The results of the study largely confirm the incentive theories which assume that fringe benefits have a positive impact on a firm's productivity. It is shown that the estimation methodology used influences this result. If existing selection biases are corrected, then the difference in productivity between firms with and without fringe benefits is smaller than in the OLS estimate. In addition to this, in some cases the difference in productivity is no longer significant after the selection adjustment. Furthermore differences are found between individual types of employee benefits.
Keywords: 330; IAB-Betriebspanel; Arbeitsanreiz; Produktivitätseffekte; Gewinnbeteiligung; Weihnachtsgeld; Urlaubsgeld; Sonderzuwendung; Kapitalbeteiligung; Prämienlohn; Anreizsystem; Produktionsfunktion; betriebliche Alterssicherung